1998
DOI: 10.2166/wst.1998.0591
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of adsorption of rice-hull activated carbon

Abstract: An experiment was conducted to compare the adsorption capacity and characteristics between activated carbon made of rice-hull(RHAC) and F-400 by Calgon to remove phenol, heavy metal and ammonia-nitrogen. While F-400 could not remove ammonia-nitrogen, RHAC was able to adsorb it. This is considered to be due to the ionic sorption capability of SiO2 remaining on the surface of RHAC. From the sorption equilibrium test, it was found that RHAC has higher adsorption capacity than F-400. In column tests, the slope of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 0 publications
2
21
0
1
Order By: Relevance
“…Adsorption is an efficient method to clean chromium (III) ions (Tarasevich and Klimova, 1999) and activated carbon is a widely employed adsorbent to remove it (Candela et al, 1995). However, because of the high cost of activated carbon, the possibilities of several wastes such as red mud (Gupta et al, 2001a) activated slag (Srivastava et al, 1997), activated carbon developed from fertilizer waste material (Srivastava et al, 1996), green algae spirogyra species (Gupta et al, 2001b), spent bleaching clay (Seng et al, 2001), bagasse fly ash (Gupta et al, 1999;Gupta and Ali, 2004) as well as rice hull and its derivatives (Kim and Choi, 1998;Srinivasan et al, 1988) have been investigated to replace it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorption is an efficient method to clean chromium (III) ions (Tarasevich and Klimova, 1999) and activated carbon is a widely employed adsorbent to remove it (Candela et al, 1995). However, because of the high cost of activated carbon, the possibilities of several wastes such as red mud (Gupta et al, 2001a) activated slag (Srivastava et al, 1997), activated carbon developed from fertilizer waste material (Srivastava et al, 1996), green algae spirogyra species (Gupta et al, 2001b), spent bleaching clay (Seng et al, 2001), bagasse fly ash (Gupta et al, 1999;Gupta and Ali, 2004) as well as rice hull and its derivatives (Kim and Choi, 1998;Srinivasan et al, 1988) have been investigated to replace it.…”
Section: Introductionmentioning
confidence: 99%
“…This finding encourages us to explore the possibility of using this low cost RHA to uptake chromium (III) ion from aqueous solution. Unfortunately, reports on the performance of the rice hull or its derivatives to remove Cr 3+ are scarce in the literature (Kim and Choi, 1998;Srinivasan et al, 1988). Srinivasan et al (1988) prepared their activated carbon from rice hull by treating it with sulphuric acid and then activating it by air.…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium data were well fitted in terms of the Freundlich and Langmuir adsorption isotherm models. The maximum adsorption capacity was relatively higher than other adsorbent material (Table 7) [38][39][40][41][42] and found to be 385 mg/g (1.86 mmol/g). The thermodynamic parameters have been obtained, and showed that the sorption process of SCNP onto lead was spontaneous and exothermic.…”
Section: Resultsmentioning
confidence: 92%
“…The renewable silica powder is mailny amorphous and more reactive than silica powder of crystalline quarts minerals. Instead of amorphous silica powder, the rice husk and straw wastes can produce active carbon powders having high surface area [2]. The ratio contents of silica and carbon of the burned high siliconeous biomasses depend on pre-teatments, burning temperatures and length of burning as reported previously by some researchers [3,4].…”
Section: Introductionmentioning
confidence: 82%